The Neolithic great goddess : a study in modern tradition - Hutton, Ronald
Modern belief in the veneration of a single Great Goddess in the European Neolithic is often accompanied by the notion that those cultures of 'Old Europe' were woman-centred in society as well as religion. What is the long history which precedes these contemporary notions? What is the complex history of their political development? A chain runs from Classical times to Marija Gimbutas (Meskell 1995) and our own day.